Pengembangan Sumber Daya Manusia Islami: Model Pembelajaran Akuntansi Syariah Di Perguruan Tinggi Islam - Dessy Handayani; Abdullah Sahroni (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2019)
The growth of Islamic financial institutions becomes a matter of interest by many groups, both from the producer and the customer. The thing that attracts the most customers is because of religious and economic factors, the factor of religiosity can be seen that Sharia financial institutions apply Sharia principles, including in terms of financial accounting (Sharia accounting) and economic factors. In terms of recording, Islamic financial institutions must have regulations to create human resources that understand Sharia principles. This research was conducted at an Islamic tertiary institution in Palembang and the respondents were 5th semester students of Islamic banking study programs. A quantitative descriptive approach is expected to produce research results that are relevant to the current needs of the world of Islamic financial institutions. This study concludes that there is a positive and significant correlation between Sharia accounting learning and Islamic human resource development